Study about Toxicity of Mentha x piperita L. - Neves, José Manuel (New Innovations in Chemistry and Biochemistry Vol. 8, 2022)
While Mentha x piperita L. is a popular herb used in the northern region of Portugal to prepare tisanes the information about its possible toxicity is scarce. The goal of this study was to assess the toxicity of the aqueous extract on the physiology, morphology and biochemistry of Tetrahymena pyriformis. Mint extract affected the generation time and growth in a dose-dependent manner. It was also observed that morphometric features of the cells of T. pyriformis were affected. The MTT assay showed a dose-dependent response of mint extracts. The usage of Mentha x piperita L leaves extract must be exercised with caution.